STRATEGI KOMUNIKASI DINAS LINGKUNGAN HIDUP (DLH) DALAM MENGIMPLEMENTASIKAN PROGRAM GREEN CITY DI KOTA TELUK KUANTAN KABUPATEN KUANTAN SINGINGI - Deri Kalianda; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Green city is a program issued by the Ministry of Environment and Forestry in 2007. This program is for local governments to implement environmentally sound development. Kuantan Singingi regency is one of the regencies that try to apply Green City concept, this program is coordinated by the Environment Agency (DLH). The purpose of this program is to realize Kuansing with the concept of Environment. This program involves many parties, namely the public, private parties, offices, and companies in Kuansing. Many implementations have been done to realize this green city, one of which is planting tree seeds on the protocol road. The purpose of this research is to know communicator strategy in implementing green city, audience strategy, message strategy and media usage in implementing green city program.This research uses qualitative research method. Informant of this research is 5 people consisting of 2 people from Environmental Office of Kuantan regency singingi and 3 people of society which is chosen by purposive. Data collection techniques used are observation, interview, and documentation. Data validity technique used in this research is triangulation and extension of participation.The result of the research shows that the communicator strategy of Environmental Office is to involve people who are experts and experienced in environment such as Environmental Science Lecturer and Environmental Expert. In addition, it also involves people who have influence on the community such as Village Heads, Adat Stakeholders and Religious Leaders. Strategy Determination of the audience by the Office of the Environment is to choose the nearest audience from downtown, the city of Kuantan Bay and surrounding areas. Consists of the general public, Office and School and Company. The Message Strategy by the Office of the Environment is by using a variety of messages, messages conveyed in seminars, training, banners, advertisements. The message in general is to realize the concept of green city kuansing. Selection of Media in implementing green city program by Environment Department is by using electronic media (Radio), online (Online news site), billboard or banner, social media (Instagram and facebook)Keywords : Communication Strategy, Green City, Kabupaten Kuantan Singingi